mRNA vaccine platforms: linking infectious disease prevention and cancer immunotherapy - Dariush Haghmorad; Majid Eslami; Niloufar Orooji; Niloufar Orooji; Iryna Halabitska; Iryna Kamyshna; Oleksandr Kamyshnyi; Valentyn Oksenych (Frontiers in Bioengineering and Biotechnology)
The advent of mRNA vaccines, accelerated by the global response to the COVID-19 pandemic, marks a transformative shift in vaccine technology. In this article, we discuss the development, current applications, and prospects of mRNA vaccines for both the prevention and treatment of infectious diseases and oncology. By leveraging the capacity to encode antigens within host cells directly, mRNA vaccines provide a versatile and scalable platform suitable for addressing a broad spectrum of pathogens and tumor-specific antigens. We highlight recent advancements in mRNA vaccine design, innovative delivery mechanisms, and ongoing clinical trials, with particular emphasis on their efficacy in combating infectious diseases, such as COVID-19, Zika, and influenza, as well as their emerging potential in cancer immunotherapy. We also address critical challenges, including vaccine stability, optimization of immune responses, and the broader issue of global accessibility. Finally, we review potential strategies for advancing next-generation mRNA vaccines, with the aim of overcoming current limitations in vaccine technology and enhancing both preventive and therapeutic approaches for infectious and oncological diseases.